Associations of plasma phospholipid cis-vaccenic acid with insulin resistance markers in non-diabetic men with hyperlipidemia - Macášek, Jaroslav; Staňková, Barbora; Žák, Aleš; Růžičková, Markéta; Brůha, Radan; Kutová, Simona; Vecka, Marek; Zeman, Miroslav (Nutrition & diabetes, 2024)
BACKGROUND: The role of fatty acids (FA) in the pathogenesis of insulin resistance and hyperlipidemia is a subject of intensive research. Several recent works have suggested cis-vaccenic acid (cVA) in plasma lipid compartments, especially in plasma phospholipids (PL) or erythrocyte membranes, could be associated with markers of insulin sensitivity and cardiovascular health. Nevertheless, not all the results of research work testify to these beneficial effects of cVA. Therefore, we decided to investigate the relations of proportion of cVA in plasma PL to markers of insulin resistance in hyperlipidemic men. SUBJECTS: In 231 men (median age 50) with newly diagnosed hyperlipidemia, we analyzed basic clinical parameters together with FA composition of plasma PL and stratified them according to the content of cVA into upper quartile (Q4) and lower quartile (Q1) groups. We examined also small control group of 50 healthy men. RESULTS: The individuals in Q4 differed from Q1 by lower plasma insulin (p < 0.05), HOMA-IR values (p < 0.01), and apolipoprotein B concentrations (p < 0.001), but by the higher total level of nonesterified FA (p < 0.01). Both groups had similar age, anthropometrical, and other lipid parameters. In plasma PL, the Q4 group had lower content of the sum of n-6 polyunsaturated FA, due to decrease of γ-linolenic and dihomo-γ-linolenic acids, whereas the content of monounsaturated FA (mainly oleic and palmitoleic) was in Q4 higher. CONCLUSIONS: Our results support hypothesis that plasma PL cVA could be associated with insulin sensitivity in men with hyperlipidemia.
Keywords: Humans; lidé středního věku; Insulin Resistance; Oleic Acids; kyseliny olejové; dospělí; lidé; Biomarkers; apolipoproteiny B; Adult; biologické markery; Male; Hyperlipidemias; Middle Aged; inzulinová rezistence; Phospholipids; Insulin; Apolipoproteins B; fosfolipidy; hyperlipidemie; mužské pohlaví; inzulin